Positioning Sowa Rigpa in India: Coalition and antagonism in the quest for recognition (Medicine Anthropology Theory, 2016)
The years leading up to the recognition of Sowa Rigpa (Tibetan medicine) by the Government of India in 2010 saw unprecedented interaction between various branches of the tradition and the state apparatus. These interactions grew particularly intense during March 2008, when two conferences focusing on related issues took place. The first referred to ‘Tibetan medicine’ and was organised by Tibetan exile institutions, while the second spoke of ‘Sowa Rigpa’ and was hosted by a coalition of Himalayan Indian associations. Through detailed ethnography of these events, this article examines the way in which a medical system was discursively constructed and positioned on the brink of state enfranchisement. It shows how ‘discourse coalitions’ and antagonisms formed during these events, and enquires as to the implications of these for the balance of power in Sowa Rigpa and for its positioning in relation to the Indian state, technoscience, and the growing market for traditional medicines.